Indonesian And Malaysia Sea Defense Strategies In Responding The South China Sea’s Threats - Reghina Rizqy Syifaranie; Buddy Suseto; Ikhwan Syahtaria (CV. AFDIFAL MAJU BERKAH, 2024)
The South China Sea is a source of conflict between China and Southeast Asian countries such as Indonesia and Malaysia because China claims the nine-dash lines that pass through the Indonesian Exclusive Economic Zone and the Malaysian territory. This area has high fishery potential and is the main route for global trade, so the maritime defense strategies of the countries concerned are very crucial. This research method uses qualitative data sources using literature studies. The results of the analysis and discussion show that there are differences between Indonesia's and Malaysia's maritime defense strategies, which are influenced by factors such as the fact that Malaysia is one of the ASEAN countries that claims the South China Sea area. However, Indonesia and Malaysia have similarities by using soft power diplomacy and track-3 multi-track diplomacy in dealing with these threats, one of which is due to the economic cooperation of the both countries with China.